TARİHSEL SÜREÇTE HAŞHAŞ (Papaver somniferum L.) VE AFYON - (:unkn) unknown (My University, 2018)
Haşhaş çok uzun yıllardır Anadolu topraklarında yetiştirilen ve çok çeşitlişekillerde istifade edilen özel bir tarım ürünüdür. Haşhaştan elde edilen afyonun vebunun zaman içerisinde değişen kullanım alanı ile söz konusu bitki, klasik bir tarımürünü olmaktan çıkmış ve ülkeleri savaşa sürükleyen, zaman zaman diplomatik krizleresebep olan bir ürün halini almıştır. Bununla birlikte kötü amaçlı kullanıma yöneliküretimin çok ciddi boyutlara ulaşmasıyla üretim ve buna bağlı sorunlar katlanarakgünümüze değin intikal etmiştir. Bu çalışmada haşhaşın ve bundan elde edilen afyonuntarihsel süreçte gelişimi ve son olarak Anadolu’daki durum ele alınmıştır.

Poppy is a special agricultural product which has been grown in Anatolian soil for many years and used for various reasons. Along with the information of that the opium obtained from poppy and its using area which has been changed in time, the plant poppy in question is no longer a classic agricultural product, and it became a product drafting countries into war and causing diplomatic crisis from time to time. In addition to these, the very significant production intended for malicious use and the problems related to this have incrementally reached the present day. In this study, the development of the poppy and the opium obtained from poppy in the historical process have been worked and in the end the situation in Anatolia handled.
Poppy (Papaver somniferum L.) And Opium in Historical Process
Keywords: Tarih